Van Bommel-Van Dam Prijs 1995. (Venlo : Museum Van Bommel Van Dam, 1995)
Bennema, Aafke ; Breevoort, Peter ; Catsburg, Sandra ; Kittelmann, Anne ; Kok, Roelof W. ; Krause, Anja ; Lemaire, Danielle ; Lemmerling, Philip ; Noort, Marieke ; Onnen, Serge ; Ovink, Henk ; Schotel, Mark ; Domis, Natasja de Sénerpont ; Smmit, John Cees ; Spitteler, Marjolein ; Wildner, Thomas ; van Wylick, Suzanne
biografie
Van Bommel-Van Dam Prijs 1995, Museum Van Bommel Van Dam, Venlo, van 17 november 1995 tot en met 14 januari 1996
Nederlands
kunstcatalogus